Heterotrophic Nitrogen Fixation at the Hyper-Eutrophic Qishon River and Estuary System - Geisler, Eyal; Bogler, Anne; Bar-Zeev, Edo; Rahav, Eyal (Frontiers in Microbiology, 2020)
Planktonic heterotrophic diazotrophs (N2-fixers) are widely distributed in marine and freshwater systems, yet limited information is available on their activity, especially in environments with adverse conditions for diazotrophy (e.g., N-rich and oxygenated). Here, we followed the localization and activity of heterotrophic diazotrophs in the hyper-eutrophic N-rich Qishon river, an environment previously considered to be unfavorable for diazotrophy. Our results indicate high heterotrophic N2 fixation rates (up to 6.9 nmol N L-1 d-1), which were 3 fold higher at an upstream location (freshwater) compared to an estuary (brackish) site. N2 fixation rates correlated positively and linearly with bacterial abundance and production measurements, as well as with transparent exopolymer particles concentration (proxy for polysaccharide matrix of aggregates). Newly developed immunolocalization approach showed that active heterotrophic diazotrophs were tightly associated with free-floating aggregates. All things considered, our results provide new insights on the activity and link of heterotrophic diazotrophs to aggregates in environments previously considered with adverse conditions for diazotrophy. However, these new insights will also be applicable to other aquatic regimes worldwide with similar N-rich/oxygenated conditions that may inhibit N2 fixation.